Integrative genomic and transcriptomic analysis of leiomyosarcoma - Chudasama, Priya; Herbst, Sophie; Kasper, Bernd; Heilig, Christoph E.; Egerer, Gerlinde; Kalle, Christof von; Eils, Roland; Stenzinger, Albrecht; Glimm, Hanno; Gröschel, Stefan; Omlor, Georg; Lehner, Burkhard; et al. (Nature Communications, 2018)
The molecular genetic landscape of leiomyosarcoma (LMS) is largely unknown. Here, the authors identify frequent DNA copy number alterations, whole-genome duplication, TP53 and RB1 inactivation, alternative telomere lengthening, and genomic imprints of defective DNA repair via homologous recombination as a potential therapeutic target in LMS patients.